'The largest volunteer life saving corps in the world': centering child caregiving in histories of U.S. human security through the Little Mothers' League. (4th May 2019) - Olson, Elizabeth
Abstract: In this article, I explore the relationship between youth, security, and caregiving through a study of the U.S. Little Mothers' Leagues, an initiative which began in New York City in 1910 with the aim of reducing infant mortality by training young girls to properly care for their infant siblings. Critical approaches to caregiving view security and insecurity as relational, drawing attention to contemporary power arrangements in the global caregiving industry and the contemporary crisis of care. However, in treating children as perpetual care recipients, it fails to provide a robust framework for understanding youth and children in historical and contemporary concerns related to human security. The history of the Little Mothers, largely children of European 'non-native white' immigrant families, illustrates the importance of children in securing population-wide well-being and the nation's status in the global competition to reduce infant mortality. When set in contrast to the eugenics-inspired Mothercraft movement, the case reveals how children and youth become enlisted into projects of national human security, and how their ambiguity as caregivers – too young according to modern childhood, yet effective lifesavers – intersects with race and gender to further obscure their status as caregiving agents